1984
DOI: 10.1016/s0022-5347(17)50648-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Prostate-Specific Antigen in Urologic Cancers

Abstract: Serum prostate-specific antigen (PA), a new tumor marker of prostate cancer, was evaluated with an enzyme immunoassay (EIA) in various urologic cancer patients and benign prostatic diseases in Japanese. Sera of prostate cancer patients before treatment (n = 27) revealed a range of PA concentrations from 0.12-23 ng/ml with a mean ( * SD) of 5.78 + 6.85 ng/ml, while that of patients with benign prostatic hypertrophy (BPH) (n = 27) showed from less than 0.10 to 2.6 ng/ml with 0.84 f 0.81 ng/ ml (mean f SD). The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1984
1984
1986
1986

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…These were of particular interest because they were apparently secreted in large quantities and because they appeared on the elearophorograms in areas relatively devoid of other .proteins, thus rendering them more accessible to isolation and purification. The larger protein (MM 33 000; PI = 6.3) may be identical to the 'prostatic specific antigen' which is currently being evaluated as a diagnostic tool in the detection of prostatic cancer (Allhoff et al 1983;Takeuchi et al 1983). The smaller of the two smaller (MM 16 000; PI = 4.8) exhibited an electrophoretic mobility similar to the rat ventral prostate lobe protein, prostatein, an observation which has also been reported previously from studies of human prostatic fluid (Carter & Resnick 1982), although the two proteins appear to be immunologically quite distinct (Pousette et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…These were of particular interest because they were apparently secreted in large quantities and because they appeared on the elearophorograms in areas relatively devoid of other .proteins, thus rendering them more accessible to isolation and purification. The larger protein (MM 33 000; PI = 6.3) may be identical to the 'prostatic specific antigen' which is currently being evaluated as a diagnostic tool in the detection of prostatic cancer (Allhoff et al 1983;Takeuchi et al 1983). The smaller of the two smaller (MM 16 000; PI = 4.8) exhibited an electrophoretic mobility similar to the rat ventral prostate lobe protein, prostatein, an observation which has also been reported previously from studies of human prostatic fluid (Carter & Resnick 1982), although the two proteins appear to be immunologically quite distinct (Pousette et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…In 29 cases of BPH raised PSA levels, but < 10 ng/ml, were found in 49% by Kuriyama et al [1982]; by contrast using the same test in 27 Japanese patients with BPH all were <2.6 ng/ml [Takeuchi et al, 1983],…”
Section: Estracytmentioning
confidence: 98%
“…Serum PSA has been reported as normal in renal and bladder cancer [Takeuchi et al, 1983] . Its potential as a marker for prostatic cancer has been studied extensively by members of the National Prostatic Cancer Project [ Wang et al, 1979;Kuriyama et al, 1982;Killian et al, 1985], They used an assay with an upper limit of normal of 2.5 ng/ml.…”
Section: Estracytmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases the clinical picture and the morphology of the tumour provide the answer, but instances remain where conventional assessments give an equivocal diagnosis. In 1979, Wang et al reported the isolation and purification of an antigen from prostatic tissue which was both organ-specific and distinct from prostate-specific acid phosphatase, and subsequently shown to be a useful serum marker in patients with prostatic carcinoma (Kuriyama et al, 1981;Takeuchi et al, 1983). The immunocytochemical localisation (Nadji et al, 1981) of this prostatespecific antigen might be used to determine the prostatic origin of a tumour.…”
mentioning
confidence: 99%